Filosofi Teras: Filsafat Kuno Untuk Ketangguhan Mental Masa Kini - Muhammad Afiqurrohman; Masduki Asbari; Umi Farida (Yayasan Aya Sophia Indonesia, 2025)
Henry Manampiring’s Filosofi Teras (2018) explores the relevance of Stoicism in addressing the challenges of modern life. This study aims to analyze the book's content using a descriptive qualitative method with the note-taking technique. The book provides practical guidance for readers to manage emotions, overcome anxiety, and enhance mental resilience. Based on the analysis, the book effectively simplifies Stoic concepts for a broader audience, though it has certain limitations, such as a lack of in-depth discussion on original Stoic philosophy. This research offers insights into how this work became a popular self-help book in Indonesia.